2020
DOI: 10.4103/nsn.nsn_34_20
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Turkish Version of King'S Parkinson's Disease Pain Scale

Abstract: Objective: Pain, a nonmotor symptom in Parkinson's disease (PD), affects approximately 40%–85% of patients and adversely affects their daily activities. Therefore, our aim was to establish the validity and reliability of the Turkish version of King's PD Pain Scale (KPDPS) and to make it available for Turkish patients with PD patients. Methods: The first phase of the study involved the translation and adaptation of the KPDPS to Turkish. For the language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The results of the present study demonstrate that KPPS-BG had a good reliability and validity. Cronbach’s α of total scale was 0.75, which indicates a good level of internal consistency similar to those reported in the original publication (0.78) [ 14 ], by Rodríguez-Violante et al (0.74) [ 15 ], and by Soyuer et al (0.827) [ 22 ]. Taghizadeh et al found Cronbach’s 0.88 [ 24 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the present study demonstrate that KPPS-BG had a good reliability and validity. Cronbach’s α of total scale was 0.75, which indicates a good level of internal consistency similar to those reported in the original publication (0.78) [ 14 ], by Rodríguez-Violante et al (0.74) [ 15 ], and by Soyuer et al (0.827) [ 22 ]. Taghizadeh et al found Cronbach’s 0.88 [ 24 ].…”
Section: Discussionsupporting
confidence: 83%
“…Available is an officially translated version in German [21]. Recently, a validated version in Turkish, Hindi and Persian were published [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study demonstrate that KPPS-BG had good reliability and validity. Cronbach's α of total scale was 0.75, which indicate good level of internal consistency similar to those reported in the original publication (0.78) [12] and by Rodríguez-Violante et al (0.74) [13], and Soyuer et al (0.827) [20].…”
Section: Discussionsupporting
confidence: 85%
“…Available is an o cially translated version in German [19]. Recently, a validated version in Turkish was published [20].…”
Section: Introductionmentioning
confidence: 99%